Lethal spots, vital secrets: medicine and martial arts in South India - Sieler, Roman (Oxford University Press, 2015)
Machine generated contents note: -- Introduction: The vital spots -- Chapter 1. Vital manifestations: marman, marmmam, and varmam spots -- Chapter 2. The vital spots: Heterogeneous theories, consistent traditions -- Chapter 3. Dispensary and training ground: Medicine and Martial Arts Intertwined -- Chapter 4. Healing the Hidden: Somatic Modes of Attending to Bodies -- Chapter 5. Virtue and Liability: The vital spots between concealment and revelation -- Chapter 6. Embodying secrecy: A moral economy of learning and the transmission of tacit knowledge -- Epilogue: From Tactility to Textuality, from Kanyakumari to the World -- Bibliography -- Index
Includes bibliographical references and index
Keywords: Schmerzpunkt; Kalaripayattu; Siddha; Distrikt Kanyakumari